2010
DOI: 10.1055/s-0036-1586357
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired hyponatremia in children: Epidemiology, pathophysiology, and prevention

Abstract: Recent observations have revealed that otherwise healthy children with acute illnesses are prone to hyponatremia due to increased arginine vasopressin production by non-osmotic stimuli. Concern has recently been raised about the potential for iatrogenic hyponatremia as a result of maintenance fluid therapy for those children. To minimize the risk of development of hospital-acquired hyponatremia in sick children receiving maintenance fluid therapy, the routine practice of administration of hypotonic fluids (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the past decade, however, it has been reported that the infusion of hypotonic IVF in otherwise healthy children with acute illnesses may cause hyponatremia named as "hospital-acquired hyponatremia" [2][3][4][5]. Though the pathophysiological basis for "hospital-acquired hyponatremia" is not fully understood, it is considered to be caused by administration of hypotonic IVF such as 0.18% saline/4% dextrose to sick children, who demonstrated increased AVP production induced by non-osmotic stimuli [2][3][4][5]. As increasing evidence has shown that hypotonic maintenance IVF can lead to potentially fatal hyponatremia and hyponatremia is a rather serious condition than previously believed [13], recommendations by Holliday and Segar for prescribing hypotonic IVF solution [1] need to be reassessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, however, it has been reported that the infusion of hypotonic IVF in otherwise healthy children with acute illnesses may cause hyponatremia named as "hospital-acquired hyponatremia" [2][3][4][5]. Though the pathophysiological basis for "hospital-acquired hyponatremia" is not fully understood, it is considered to be caused by administration of hypotonic IVF such as 0.18% saline/4% dextrose to sick children, who demonstrated increased AVP production induced by non-osmotic stimuli [2][3][4][5]. As increasing evidence has shown that hypotonic maintenance IVF can lead to potentially fatal hyponatremia and hyponatremia is a rather serious condition than previously believed [13], recommendations by Holliday and Segar for prescribing hypotonic IVF solution [1] need to be reassessed.…”
Section: Discussionmentioning
confidence: 99%
“…The following patients in states of AVP excess were excluded from the analysis: children requiring water restriction because of the high risk of developing syndrome of inappropriate antidiuretic hormone secretion, such as meningitis, encephalitis, acute bronchiolitis or post-operative condition [5]; children with evident dehydration; children demanding only small amount of IVF for maintenance fluid therapy (at a rate of less than 10 ml/hour). Exclusion criteria also included renal disease, cardiac dysfunction, and known adrenal dysfunction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hyponatremia in nearly all patients with KD is mild and asymptomatic, some patients develop profound hyponatremia and CNS involvement. Moreover, hypotonic intravenous fluid infusion in patients with hyponatremia may cause more profound hyponatremia and can contribute to deterioration in the patient's condition [65]. The management of hyponatremia in KD should include the use of isotonic fluids, as well as treatment targeting etiologies of hyponatremia [27,65].…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Moreover, hypotonic intravenous fluid infusion in patients with hyponatremia may cause more profound hyponatremia and can contribute to deterioration in the patient's condition [65]. The management of hyponatremia in KD should include the use of isotonic fluids, as well as treatment targeting etiologies of hyponatremia [27,65]. Recently, Kaneko and colleagues [66] compared the serum sodium levels in KD patients with hyponatremia who received intravenous immunoglobulin (IVIG) preparations containing high (0.9%) or trace concentrations of sodium, and reported the following: administration of IVIG preparations increased the serum sodium levels in patients receiving preparations with high concentrations of sodium, but not trace concentrations of sodium; the median serum sodium level in patients receiving preparations with high concentrations of sodium was significantly higher than that in patients receiving trace concentrations of sodium; and the trace IVIG products had an adverse effect on hyponatremia in KD.…”
Section: Clinical Perspectivementioning
confidence: 99%